A new barbeled goby from south China (Teleostei: Gobiidae) - Cui, Rongfeng; Pan, Yashu; Yang, Xinming; Wang, Yingyong (Zootaxa, 2013)
A new goby species Tridentiger radiatus sp. nov. is described from Zhuhai, Guangdong Province of China. The new spe-cies, found in sympatry with a widely distributed barbeled congener Tridentiger barbatus (Günther, 1861), is one of the only two Tridentiger species known to possess mandibular and cheek barbels. Tridentiger radiatus is diagnosed by having higher longitudinal and transverse scale counts, less developed barbels, unmottled colouration compared to T. barbatus, and 3 dusky radiating infraorbital bands. Partial 12s rDNA sequence data obtained from 5 individuals of T. radiatus and 2 individuals of T. barbatus, together with published sequence data of other congeners confirmed validity of the new spe-cies. The divergence between T. radiatus and T. barbatus well exceeds the divergence of other sister taxa in the same ge-nus. Monophyly of the two barbeled species is supported.